Donald J. MacDonald papers - MacDonald, Donald J. (Donald John), 1908-
Chiefly correspondence, biographical material, and military papers relating to MacDonald's naval career, especially during World War II. The collection documents his tour of duty as a naval observer at the U.S. embassy in London (1940-1942), the fitting out of the U.S.S. O'Bannon at Bath Iron Works (Maine) in 1942 and his subsequent command of that ship in the South Pacific, his attachment to Gen. Dwight D. Eisenhower's staff in the Allied attempt to cross the Rhine River into Germany in 1945, and his command of Harry S. Truman's presidential yacht, the U.S.S. Williamsburg, from 1948 to 1951. Includes histories and other records relating to the California, Heermann, Helena, and Missouri, U.S. ships also commanded by MacDonald; transcripts of oral history interviews; and wartime comic books depicting the exploits of MacDonafd and the O'Bannon. His brother, U.S. Army Air Forces pilot Charles H. MacDonald, is represented in the biographical material.
U.S. naval officer. Died 1997.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Eisenhower, Dwight D. -- 1890-1969.; MacDonald, Charles H., -- 1915-; Truman, Harry S., -- 1884-1972.; Bath Iron Works; California (Battleship : BB-44); Heermann (Destroyer); Helena (Heavy cruiser); Missouri (Battleship : BB 63); O'Bannon (Destroyer : DD-450); United States. -- Army Air Forces; United States. -- Navy -- Officers; Williamsburg (Ship); Diplomatic and consular affairs, American -- Great Britain; Military attachés -- Great Britain; Presidential yachts; Shipbuilding industry -- Maine; World War, 1939-1945 -- England -- London; World War, 1939-1945 -- Amphibious operations; World War, 1939-1945 -- Campaigns -- Germany; World War, 1939-1945 -- Campaigns -- Rhine River Valley; World War, 1939-1945 -- Campaigns -- South Pacific Ocean; World War, 1939-1945 -- Comic books, strips, etc; World War, 1939-1945 -- Naval operations; Naval officers